Hubungan Kualitas Tidur dengan Kadar Gula Darah Sewaktu Pada Lansia dI Panti Jompo Tresna Werda Kota Bengkulu - Rusdani Rusdani; Nopri Esmiralda; Kurnia Yuliana Febrianti (Universitas Batam, 2022)
Background: Blood sugar level is the amount of glucose in blood plasma. Lack or excess of blood sugar levels in the body is influenced by several factors such as diet, age, lack of sleep and physical activity. A person is said to have hyperglycemia, especially if his blood sugar level is far above the normal value, while hypoglycemia is a condition where a person experiences a decrease in blood sugar values ​​below normal. Methods: This research is an analytic observational study with a cross sectional research design. This research was conducted at Nursing House Tresna Werda Of Bengkulu in Desember 2021. The sample in this study was 67 respondens. The sampling technigue is total sampling using inclusion and exclusion criteria. To determine the relationship between Sleep Quality and Blood Sugar Level, the data analysis used was the Chi-squere test. Result : The findings reveal those with good sleep quality and good blood sugar levels are 13 (61.9%) respondents, with good sleep quality and poor blood sugar levels are 8 (38.1%); 6 people (17.1%) with poor sleep quality and good blood sugar levels, while the respondents with poor sleep quality and poor blood sugar levels ere 29 people (82.9%). The results of the Chi-square statistical test obtained p value = 0.001 (p <0.05), so Ha is accepted and Ho is rejected. Conclusion : In conclusion, the findings suggest significant correlation of Sleep Quality and Blood Sugar Level In The Elderly In Nursing House Tresna Werda Of Bengkulu Year 2021